Between the local, national and global: The problem of “regional identities” - Kowalska, Wioletta Małgorzata (Creativity Studies, 2010)
The main objective of the paper is to examine the concepts of region and regional identity in order to point out their political, social and theoretical/philosophical opportunity, and also their highly problematic character, especially in the current Eastern European context. The author tries to determine the contents of the concept of region from phenomenological perspective and shows that it is hardly possibly because, in practice, “region” refers more to arbitrary political and administrative criteria than to what can be experienced as a common “surrounding world”. The examples of regions analyzed in the paper are those of the infra‐state Polish region Podlasie and of the supra‐state Euregion Neman. In conclusion, the author claims that the opposition cultural/political, or experienced/constructed, should be mediated by European legal and moral rules. It is also claimed that only awareness of difficulties connected with the project of regions can allow their construction in a realistic, not arbitrary and not utopian way. Tarp lokalumo, nacionalumo ir globalumo: regioninių tapatumų problema Santrauka. Pagrindinis straipsnio tikslas – išnagrinėti regiono ir regioninio tapatumo sampratas, siekiant ne tik išsiaiškinti jų politinę, socialinę ir teorinę bei filosofinę esmę, bet ir išties problemišką pobūdį, ypač dabartiniame Rytų Europos kontekste. Autorė siekia apibrėžti regiono sampratos turinį iš fenomenologinės perspektyvos ir parodo, kad tai vargu ar įmanoma, nes praktiniu požiūriu regionas labiau nurodo politinius ir administracinius kriterijus, o ne tai, kas gali būti vertinama kaip supantis pasaulis. Straipsnyje analizuojami du regionai – lenkų infranacionalinis Palenkės regionas ir supranacionalinis Nemuno euroregionas. Tvirtinama, kad kultūros bei politikos ir patirties bei supratimo prieštaravimus turi derinti Europos įstatymai ir moralės normos. Autorė teigia, kad tik kylančių sunkumų dėl regionų tyrimo įsisąmoninimas leidžia jų realų, o ne arbitralinį ar utopinį konstravimą. Reikšminiai žodžiai: civilizacija, kultūra, globalizacija, tapatumas, tauta ir valstybė, fenomenologija, politika, regionas. First published online: 10 Feb 2011